The role of the social worker in the provision of psychosocial care of cancer patients. (The Journal of Psychology and Sociology, 2015)
The article is devoted to the definition of the role of social work in health care facilities, specializing in the treatment of cancer sick children. Modern health care pays special attention to cancer, the development of medicine in this area, but is still little development of social and psycho logical support to patients. The growing number of people with cancer in Kazakhstan and, in particular, sick children, social problems of the child and his family, accompanied the disease, require the active participation of the specialist in social work. The authors point out that the family is in need of social assistance at different stages of a child’s illness. On the basis of research in pediatric oncology it is identified the main challenges faced by the family in the process of admission of the child with cancer. The types of social and psychological assistance received by the child and his family at the place of treatment, and ways to improve it are analyzed. The need of implementation of the position of social worker along with the psychologist in hospitals, assisting with cancer, is proved on the base of results of the survey.
Keywords: medicalsocial work; social worker; social work with can cer sick children; social work with family.